Deregulation of miR-128 in Ovarian Cancer Promotes Cisplatin Resistance. Issue 8 (1st October 2014) - Li, Bing; Chen, Hong; Wu, Nan; Zhang, Wen-Jing; Shang, Li-Xin
Abstract : Objective: Platinum-based chemotherapy is the standard treatment in advanced ovarian cancer, but most patients will relapse with drug-resistant disease. MicroRNAs have been demonstrated to function in chemoresistance in cancers. In this study, we focused on the role of miR-128 in cisplatin-resistant ovarian cancer. Materials and Methods: The expression of miR-128 RNA and its targeted genes, the polycomb ring finger oncogene Bmi-1 and ATP-binding cassette subfamily C member 5 (ABCC5), were investigated in the epithelial ovarian cancer cells and ovarian carcinomas. Results: miR-128 expression was significantly reduced in the cisplatin-resistant human epithelial ovarian cancer cell line SKOV3/CP compared with parental SKOV3 cells and decreased upon treatment with cisplatin in a concentration-dependent manner in SKOV3, OVCAR3, and PEO14 cells. Overexpression of miR-128 resensitized SKOV3/CP cells to cisplatin and reduced the expression of cisplatin-resistant–related proteins ABCC5 and Bmi-1, whereas miR-128 inhibitors increased cisplatin resistance in SKOV3 cells. Cisplatin combined with miR-128 agomirs inhibited the growth of SKOV3/CP xenograft tumors more effectively than cisplatin alone. Diminished expression of ABCC5 and Bmi-1 and higher cisplatin concentrations were observed in tumor tissue of mice treated with miR-128 agomirs in addition to cisplatin. Conclusions: Taken together, our findings suggest that miR-128 may act as a promising therapeutic target for improvement of tumor sensitivity to cisplatin.